Finnish primary school student teachers’ systems thinking regarding sustainability in connection with reproduction, biodiversity and sustainable development - Yli-Panula, Eija; Södervik, Ilona; Jeronen, Eila; Rantala, Hanna (University of Oslo, 2025)
Systems thinking is considered an important skill when teaching biology and sustainable development in the 21st century. The key to understanding biodiversity and thus sustainability in biology is understanding reproduction as a phenomenon. The aim of this study is to analyse student teachers’ systems thinking levels regarding sustainability in connection with reproduction, biodiversity and sustainable development. Second-year primary school student teachers from one Finnish university (N = 174) answered in a questionnaire, and their open-ended answers were categorized using content analysis. The results indicate that most of the student teachers had a relatively low level of systems thinking concerning sustainable development and its relation to the concepts of biodiversity and reproduction. The study also showed that student teachers with higher interest towards biology had a more sophisticated level of systems thinking. Teaching that emphasizes specific systems thinking skills and a comprehensive understanding of the broa- der context is essential for fostering an understanding of sustainability.